2016
DOI: 10.1016/j.molcata.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical study of CO2 and CO hydrogenation on Cu(111) surfaces doped with Ga, Mg, and Ti

Abstract: DFT methods were used to analyze metal (M)-doped Cu(111) surfaces to identify surface alloys that could catalyze the hydrogenation of CO2. The adsorption of relevant species for CO2/CO hydrogenation were studied on Cu(111) surfaces doped with Ga, Mg, and Ti. Preferred adsorption sites, geometries, and binding energies for relevant intermediates were determined. A systematic study of the thermochemistry of plausible surface reactions for CO2/CO hydrogenation on Ga/Cu(111), Mg/Cu(111), and Ti/Cu(111) was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…It is well known that CO is an electron-deficient molecule and prefers to adsorb on the surface with high surface electron density, and a strong basic surface usually means a high surface electron density. , Meanwhile, the adsorption of CO on Cu was enhanced due to the strong basic surface, which inhibited the production of CO from the reverse water gas shift and the methanol dissociation in the hydrogenation of CO 2 to methanol and then increased the selectivity to methanol . In addition, the adsorbed CO also reacted with dissociated hydrogen on the Cu surface to methanol . Therefore, the catalyst CZAZ-7 with the strongest surface basicity had the highest methanol selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that CO is an electron-deficient molecule and prefers to adsorb on the surface with high surface electron density, and a strong basic surface usually means a high surface electron density. , Meanwhile, the adsorption of CO on Cu was enhanced due to the strong basic surface, which inhibited the production of CO from the reverse water gas shift and the methanol dissociation in the hydrogenation of CO 2 to methanol and then increased the selectivity to methanol . In addition, the adsorbed CO also reacted with dissociated hydrogen on the Cu surface to methanol . Therefore, the catalyst CZAZ-7 with the strongest surface basicity had the highest methanol selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…7 In addition, the adsorbed CO also reacted with dissociated hydrogen on the Cu surface to methanol. 36 Therefore, the catalyst CZAZ-7 with the strongest surface basicity had the highest methanol selectivity.…”
Section: Physical and Structuralmentioning
confidence: 98%
“…Density functional theory (DFT) calculations have become powerful tools to investigate the theoretical chemical reaction mechanisms of methanol synthesis via the hydrogenation of CO 2 at the atomic level. , Significant efforts have focused on clarifying the mechanisms on different metal surfaces, such as Cu, , Cu 29 , Ni, Pd/oxides, and Cu alloys. The mechanism and selectivity of CO hydrogenation on pure Pd surfaces have been studied . It confirmed that the selectivity of the pure Pd catalysts was toward forming methanol rather than forming methane.…”
Section: Introductionmentioning
confidence: 95%
“…Experimentally, the hydrogenation and hydrolysis of CO without the assistance of any catalyst are difficult to achieve. Thus, a variety of heterogeneous and homogeneous catalytic processes have been adopted till date to convert CO containing gases (syn‐gas and water‐gas) into the aforementioned organic molecules. In 1921, Patart first reported the synthesis of methanol from CO and H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…reported the hydrogenation of CO mediated by Cu−Ni bimetallic surface from both the experimental as well as theoretical perspectives. Santiago‐Rodriguez et al . investigated the catalytic performance of metal (Ga, Mg and Ti)‐doped Cu(111) surfaces in the hydrogenation of CO 2 and CO employing DFT methods.…”
Section: Introductionmentioning
confidence: 99%